A PROSPECTIVE ANALYSIS OF INTRA-OPERATIVE FINDINGS AND COMPLICATIONS IN CASE OF REPEAT CAESAREAN SECTION. - Shivani Siddhpura; Pallavi Ninama (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Caesarean section (CS) is performed to save life of pregnant patient as well as foetus with a continuously increasing incidence for the last two decades giving the women, an obstetrical status of “previous caesarean section.” However, CS is associated with increased risk of maternal and perinatal morbidity and mortality. A prospective observational study carried out at GMERS Medical College, Sola, Ahmedabad, Gujarat, India from October 2020 to October 2021 with a sample size of 200. The observed intra-operative findings were analysed in relation to number of previous caesarean sections and intraoperative complications encountered in repeat caesarean section in comparison to primary LSCS. Suitable statistical tests of comparison were done. Statistical significance was taken as P< 0.05. The data was analysed using epi info 7.2.5.0. Comparison was done between 74 primary LSCS and 126 previous > 1 LSCS. The occurrence of intra-op complications like bladder injury, uterine dehiscence, extension of uterine incision and morbidly adherent placenta was statistically significant (p 2 LSCS group as compared to previous 1 LSCS and primary LSCS. Most of the patients in both the study groups had a good maternal outcome (97.30% in primary LSCS and 92.06% in previous > 1 LSCS). It was concluded that repeat caesarean sections are associated with increased intra-operative complications & maternal morbidity. The perinatal morbidity associated with repeat caesarean section can be reduced by educating public regarding the importance of antenatal care, detection of high-risk cases, making timely referrals and limiting the number of primary LSCS.